Angular flux creep contributions in YBa(2)Cu(3)O(7−δ) nanocomposites from electrical transport measurements - Vallès, F. (Sci Rep, 2018)
The shape of the electric-field—current-density (E-J) curve is determined by flux pinning and also by dynamics of vortices. Here, we propose a novel methodology to study the normalized flux creep rate S in YBa(2)Cu(3)O(7−δ) measured from E-J curves obtained by electrical transport measurements that provides a fast and versatile way to foresee the flux magnetic relaxation in films and disentangle angular flux creep contributions by the scaling of the isotropic contribution of S. After a detailed comparison of various pristine and nanocomposite films with differentiated nanostructures, we focus on the roles that intrinsic pinning and stacking faults (YBa(2)Cu(4)O(8)-intergrowths) play when the magnetic field is applied parallel to the superconducting CuO(2) planes. This study reveals that the emerging intergrowths provide advanced pinning properties that additionally reduce the thermal activated flux magnetic relaxation. For this purpose, creep analysis becomes a very appropriate tool to elucidate the dominance of the different pinning sites at different regions of the magnetic-field—temperature diagram.